Search for the standard model higgs boson in the ZH→νν̄ bb̄ channel in 5.2fb-1 of pp̄ Collisions at √s=1.96TeV - Abazov, V. M. (2010)
A search is performed for the standard model Higgs boson in 5.2fb -1 of pp̄ collisions at √s=1.96TeV, collected with the D0 detector at the Fermilab Tevatron Collider. The final state considered is a pair of b jets and large missing transverse energy, as expected from pp̄→ZH→νν̄bb̄ production. The search is also sensitive to the WH→νbb̄ channel when the charged lepton is not identified. For a Higgs boson mass of 115 GeV, a limit is set at the 95% C.L. on the cross section multiplied by branching fraction for [pp̄→(Z/W)H](H→bb̄) that is a factor of 3.7 larger than the standard model value, consistent with the factor of 4.6 expected. © 2010 The American Physical Society.